Global Variations in Cesarean Section Rates: A Systematic Review and Meta-Analysis - Malik, Salma; Ishaq, Sarwat; Farzooq, Hira (Indus Journal of Bioscience Research, 2025)
Cesarean section (CS) rates have risen globally over the past few decades, with significant variations across countries, healthcare systems, and socioeconomic contexts. This systematic review and meta-analysis aims to comprehensively compare CS rates worldwide, examining disparities between developed and low- to middle-income countries (LMICs), as well as differences between private and public healthcare facilities. Additionally, the study investigates key determinants influencing CS rates, including maternal age, socioeconomic status (SES), and access to healthcare services. A thorough search of observational and cohort studies published between 2000 and 2024 yielded 13 relevant studies for analysis. The findings reveal a pronounced divide in CS utilization: high-income nations, particularly in Europe and North America, exhibit substantially higher rates compared to LMICs, where resource constraints and limited surgical capacity restrict access. Meta-regression analysis identifies maternal age and SES as critical predictors of CS likelihood, with older women and those from higher socioeconomic backgrounds more likely to undergo the procedure. Furthermore, private hospitals consistently report significantly higher CS rates than public institutions, suggesting that financial incentives and patient preferences may contribute to overutilization in certain settings. This study underscores the dual challenge in global maternal healthcare—addressing the overuse of medically unnecessary cesarean deliveries in high-resource settings while ensuring life-saving access in underserved regions. Striking this balance is essential to optimizing maternal and neonatal outcomes, reducing preventable mortality, and promoting equitable obstetric care worldwide.